Upstreamness, Wages and Gender: Equal Benefits for All? - Nicola Gagliardi; Benoît Mahy; François Rycx (Institute of Labor Economics (IZA), 2019)
This paper provides first evidence on the impact of a direct measure of firm-level upstreamness (i.e. the steps before the production of a firm meets final demand) on workers' wages. It also investigates whether results vary along the earnings distribution and by gender. Findings, based on unique matched employer-employee data relative to the Belgian manufacturing industry for the period 2002-2010, show that workers earn significantly higher wages when employed in more upstream firms. Yet, the gains from upstreamness are found to be very unequally shared among workers. Unconditional quantile estimates suggest that male top-earners are the main beneficiaries, whereas women, irrespective of their earnings, appear to be unfairly rewarded. Quantile decompositions further show that these differences in wage premia account for a substantial part of the gender wage gap, especially at the top of the earnings' distribution.
Keywords: F61; F66; J16; J31; 330; upstreamness; global value chains; wages; gender